2014
DOI: 10.4322/rca.1064
|View full text |Cite
|
Sign up to set email alerts
|

Condicionamento osmótico na qualidade fisiológica de sementes de cebola

Abstract: RESUMO: Na cultura da cebola, são constantes os problemas relativos ao desempenho das sementes no campo, justifi cando-se o uso de técnicas que aumentem a porcentagem de germinação das sementes e a emergência das plântulas. O objetivo deste trabalho foi avaliar o efeito do condicionamento osmótico em sementes de cebola com nitrato de potássio e polietileno glicol 6000 em diferentes concentrações e períodos de condicionamento. Para tanto, sementes da cv. Baia Periforme foram condicionadas em soluções de PEG 600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(20 reference statements)
1
2
0
1
Order By: Relevance
“…There was, therefore, an interdependency between the accessions and priming treatments for the evaluated traits. This performance has also been observed in other works, for accessions of P. guineense (SANTOS et al, 2015) and varieties of Solanum sessiliflorum (PEREIRA et al, 2012) and Stryphnodendron spp. (KISSMANN et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…There was, therefore, an interdependency between the accessions and priming treatments for the evaluated traits. This performance has also been observed in other works, for accessions of P. guineense (SANTOS et al, 2015) and varieties of Solanum sessiliflorum (PEREIRA et al, 2012) and Stryphnodendron spp. (KISSMANN et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Thus, our results corroborate those obtained by Santos et al (2015) for the same species, and partially corroborate those observed with other species, such as Stryphnodendron spp. (KISSMANN et al, 2010), Solanum sessiliflorum (PEREIRA et al, 2012), and Myracrodruon urundeuva (VIRGENS et al, 2012), in all of which the priming with PEG 6000 acted negatively on the increase in germination percentage, germination speed, and germination speed index. Such behavior was only observed in accession Y93 seeds; in the other two accessions, priming influenced these parameters positively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para tal, muitos estudos têm buscado reduzir o tempo necessário entre a semeadura e a emergência das plântulas, bem como para aumentar a tolerância das sementes às condições adversas durante a germinação. Alguns tratamentos como o uso do tratamento térmico e o condicionamento osmótico têm se mostrado eficientes nesse sentido, apresentando resultados promissores com sementes de diversas espécies (OLIVEIRA; GOMES FILHO, 2010;PEREIRA et al, 2012;MORAIS et al, 2014). Welter et al (2011), avaliando a germinação de sementes de maracujá-amarelo em função de tratamentos térmicos, concluíram que o tratamento térmico das sementes a 40 ºC por 15 minutos resulta em germinação aproximada de 75% e maior uniformidade de plântulas.…”
Section: Introductionunclassified